A novel antigen delivery system induces strong humoral and CTL immune responses. (July 2017) - Yang, Zishan; Xu, Miaomiao; Jia, Zhenghu; Zhang, Yuting; Wang, Li; Zhang, Hongru; Wang, Jingya; Song, Mei; Zhao, Yapu; Wu, Zhenzhou; Zhao, Liqing; Yin, Zhinan; et al.
Abstract: New strategies with the ability to enhance both the humoral and cellular immune responses remain a priority for the development of future therapeutic cancer vaccines. In this study, we took advantage of β-glucan particles (GPs) derived from Saccharomyces cerevisiae baker's yeast and a novel reverse micro-emulsion method to prepare an antigen-loaded GP carrier system for dendritic cell (DC) specific antigen delivery, followed by careful evaluation of the immune functions of the prepared particles in initiating both the humoral and cellular immune responses through in vitro and in vivo experiments. The prepared particles greatly promoted DC activation and cytokine production and cross presented the antigen to CD8 cells, inducing very strong OVA specific humoral and cellular immune responses. Treatment with these particles significantly prevented the growth of implanted EG7-OVA tumors in a prophylactic and pre-established tumor model. These results suggest that our strategy may be able to be utilized as a promising platform for cancer immunotherapy.